2020
DOI: 10.3390/jmse8050367
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Operational Efficiency Considering Safety Factors as an Undesirable Output for Coastal Ferry Operators in Korea

Abstract: In the maritime transportation services industry, marine accidents may lead to fatalities, injuries, and property losses. Coastal ferry operators experience marine accidents and must pay attention to safety to guarantee the sustainability of their business. This study is aimed at analyzing the operational efficiency of coastal ferry operators in Korea from a safety perspective. We designed two slack-based measure of efficiency (SBM) models. One is a normal SBM, which includes only the total passenger volume as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…We conducted a satisfaction survey focused on the passengers' walkways installed inside and outside of the terminals. IPA is a quantitative approach for measuring people's feelings about certain characteristics of an issue or a thing [30,31]. IPA is beneficial because it generates a clear picture of how important certain elements are compared to the satisfaction they give to clients, customers, or services [32][33][34].…”
Section: Passenger Satisfaction In the Built Environmentmentioning
confidence: 99%
“…We conducted a satisfaction survey focused on the passengers' walkways installed inside and outside of the terminals. IPA is a quantitative approach for measuring people's feelings about certain characteristics of an issue or a thing [30,31]. IPA is beneficial because it generates a clear picture of how important certain elements are compared to the satisfaction they give to clients, customers, or services [32][33][34].…”
Section: Passenger Satisfaction In the Built Environmentmentioning
confidence: 99%
“…j: jth coastal ferry operators (j = 14) apply the results of the study by Kim et al [65] conducted by the author, as shown in Table 3.…”
Section: Var Descriptionmentioning
confidence: 99%
“…Correspondingly, weights derived from fuzzy AHP methods with extent analysis [21] and Javanbarg, Scawthorn et al [22]'s method with particle swarm optimization are compared and discussed. Contemporary studies using fuzzy AHP in the marine sector include the following: Jung, Kim et al [23]'s study on the driving factors in low cost freight carriers in Korea; Hart, Adebiyi et al [24]'s study on ferry commuter preferences in Lagos; Kim, Lee et al [25]'s assessment of the operational efficiency considering safety factors in Korea.…”
Section: Introductionmentioning
confidence: 99%